Prevalence of Hepatic and Splenic Melioidosis: A Systematic Review and Meta-Analysis - Jongkonnee Thanasai; Anchalee Chittamma; Supphachoke Khemla; Atthaphong Phongphithakchai; Moragot Chatatikun; Jitbanjong Tangpong; Sa-ngob Laklaeng; Jirart Songsri; Wiyada Kwanhian Klangbud (International Journal of Environmental Research and Public Health, 2026)
Background: Melioidosis is a potentially life-threatening infection caused by Burkholderia pseudomallei. Hepatic and splenic involvement are recognized manifestations of disseminated melioidosis; however, reported prevalence varies considerably across studies, and no quantitative synthesis has been available. This systematic review and meta-analysis aimed to estimate the pooled prevalence of hepatic, splenic, and concomitant hepatosplenic involvement in patients with melioidosis. Methods: A systematic search of PubMed, Embase, and Scopus was conducted from database inception to May 2026, following the PRISMA 2020 guidelines. Observational studies reporting hepatic and/or splenic involvement among patients with confirmed melioidosis were eligible. Random-effects meta-analyses were performed to estimate pooled prevalence with 95% confidence intervals (CIs). Subgroup analyses were conducted according to geographic region and age group. Methodological quality was assessed using the Joanna Briggs Institute critical appraisal checklist. Results: Fourteen eligible studies involving 1844 patients with melioidosis were included. The pooled prevalence of hepatic involvement was 11% (95% CI, 6–18%; I2 = 84.8%), splenic involvement was 15% (95% CI, 7–27%; I2 = 95.8%), and concomitant hepatosplenic involvement was 13% (95% CI, 4–34%; I2 = 89.5%). Subgroup analyses demonstrated significantly higher pooled prevalence of hepatic and splenic involvement in Southeast Asia than in Oceania (p = 0.0164 and p = 0.0003, respectively). No significant differences were observed between adult and pediatric populations for hepatic (p = 0.1607) or splenic involvement (p = 0.8243). Most included studies were judged to have a moderate risk of bias, and no evidence of small-study effects was identified for analyses of hepatic or splenic involvement. Conclusions: Hepatic and splenic involvement are common manifestations of melioidosis, affecting approximately one in nine and one in seven patients, respectively. Significant geographic variation suggests that disease burden is greater in Southeast Asia than in Oceania. These findings support the routine consideration of abdominal imaging in patients with suspected or confirmed melioidosis, particularly in endemic regions, to facilitate early recognition of visceral involvement. Further prospective multicenter studies using standardized imaging protocols are needed to refine prevalence estimates and improve understanding of hepatosplenic melioidosis.